Compliance with diagnostic examination in mass screening for colorectal cancer - KONNO, Yutaka; AIDA, Shigemitu; MORIMOTO, Tomizo; SHIMADA, Takenobu; KINOUCHI, Yoshitaka; SHIBUYA, Daisuke; HIWATASHI, Nobuo (Journal of Gastroenterological Mass Survey, 2003)
Only about 60% of subjects whose screening tests are positive have diagnostic examination in mass screening for colorectal cancer in Japan. To improve the compliance with diagnostic examination, we performed following four strategies: 1) to organize community meetings to explain about diagnostic examination for subjects whose screening tests are positive; 2) to provide opportunities to make appointments for diagnostic examinations at the community meetings; 3) to shorten the interval from screening test to diagnostic examination: and 4) to encourage subjects who did not have diagnostic examinations within about three months after notice of the test results to receive the examinations. During April, 1993 through March, 2001, a total of 421674 immunological fecal occult blood tests were performed and 15136 (3.6%) were tested positive. Among the subjects with positive results, 95.3% of them had diagnostic examinations. Although in a certain area the method of diagnostic examination was changed from flexible sigmoidoscopy and barium enema to total colonoscopy, the compliance rate for diagnostic examination did not decrease. These results suggest that these four strategies are important in order to improve the compliance with diagnostic examination, and that total colonoscopy is acceptable as the method of diagnostic examination.